Chrysanthemum [videorecording (DVD)] : --and more mouse mayhem - Streep, Meryl; Parker, Sarah Jessica; Hurt, Mary Beth; Woertendyke, Ruis; Leebaert, Melissa; Brooks, Jeff (Narrator); Henkes, Kevin; Henkes, Kevin; Henkes, Kevin; Kent, Jack, 1920-1985; McCarty, Peter; Schories, Pat (Scholastic storybook treasures., 2011)
6 stories on one DVD with narration by Meryl Streep, Sarah Jessica Parker, Mary Beth Hurt ... and others.